Aortopathy - Niwa, Koichiro; Kaemmerer, Harald (Springer Japan : Imprint: Springer, 2017)
This is the first textbook to focus on Aortopathy, a new clinical concept for a form of vasculopathy. The first section of the book starts from discussing general concept and history of Aortopathy, and then deals with its pathophysiology, manifestation, intrinsic factor, clinical implication, management and prevention. The second part closely looks at various disorders of the Aortopathy such as bicuspid aortic valve and coarctation of aorta. The book editors have published a lot of works on the topic and have been collecting relating data in the field of congenital heart disease for the past 20 years, thus present the book with confidence. The topic - an association of aortic pathophysiological abnormality, aortic dilation and aorto-left ventricular interaction - is getting more and more attention among cardiovascular physicians. This is the first book to refer for cardiologists, pediatric cardiologists, surgeons, ACHD specialists, etc. to acquire thorough knowledge on Aortopathy. .
Keywords: Medicine.; Cardiology.; Pediatrics.; Cardiac surgery.; elektronické knihy; electronic books